1998
DOI: 10.1007/bf02672510
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between bone mineral density and ultrasound in postmenopausal and osteoporotic women

Abstract: The aim of this cross-sectional study was to use a novel method of data analysis to demonstrate that patients with osteoporosis have significantly lower ultrasound results in the heel after correcting for the effect of bone mineral density (BMD) measured in the spine or hip. Three groups of patients were studied: healthy early postmenopausal women, within 3 years of the menopause (n = 104, 50%), healthy late postmenopausal women, more than 10 years from the menopause (n = 75, 36%), and a group of women with os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 16 publications
2
10
1
1
Order By: Relevance
“…Calculating the Standardized Precision transforms the precision of SOS to about 3 times that of AP spine BMD. The long-term Standardized Precision for the QUS parameters ranged from 2 to 3 times that of AP spine BMD, which is consistent with the findings of a number of short-term studies [10,18]. This means that for a given rate of change, the long-term Standardized Precision of QUS is 2-3 times that of AP spine DXA, in a given individual.…”
Section: Qus and Monitoring Of Treatmentsupporting
confidence: 64%
See 2 more Smart Citations
“…Calculating the Standardized Precision transforms the precision of SOS to about 3 times that of AP spine BMD. The long-term Standardized Precision for the QUS parameters ranged from 2 to 3 times that of AP spine BMD, which is consistent with the findings of a number of short-term studies [10,18]. This means that for a given rate of change, the long-term Standardized Precision of QUS is 2-3 times that of AP spine DXA, in a given individual.…”
Section: Qus and Monitoring Of Treatmentsupporting
confidence: 64%
“…This advantage coupled with the fact that measurements are ionizing radiation free, and the machines relatively inexpensive and small enough to be portable, makes it a potentially valuable tool both for fracture risk assessment and for measuring the response to therapy. Currently QUS parameters can distinguish between normal and osteoporotic subjects [9,10] and recent studies have reported that QUS techniques are able to predict hip and vertebral fractures [11][12][13]. However, the usefulness of QUS in long-term monitoring has yet to be defined [14,15].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…KEY WORDS: Bone densitometry; Osteoporosis; Osteomalacia; Densitometry. 0.4 to 0.7 [13][14][15][16][17][18][19][20] and are higher when measurements are performed on the same skeletal site. 21 The purpose of this study was to utilize ultrasonographic techniques to differentiate qualitative alterations of bones with the same mineral content.…”
mentioning
confidence: 99%
“…BMD measured by QUS has shown strong relationship with age, gender, body mass index (BMI), waist to hip ratio (WHR), smoking status, frequency of exercise etc. 1 There are studies [11][12][13][14] pointing to limitations of using calcaneal USBMD in screening, monitoring of therapy. Apart from the limitations intrinsic to In both the villages dietary habits, the daily dietary intake of calcium, phosphorus and phytates were documented by recalling the diet consumed in the previous 5 to 7 days.…”
Section: Introductionmentioning
confidence: 99%